Development and field evaluation of blades with different lifting angles for mulching oil palm fronds prior to seedling planting - Jahun, Bala Gambo (2018)
In the oil palm industry, only 10% palm oil is produced and the other 90% is in the form of wastes which generates the largest amount of biomass, estimated at 80 million dry tonnes annually. The conventional technique of clearing old oil palm residues during pruning and subsequent field upkeep in Malaysia was the “chip and burn method”. With the ban on open burning, the chipped palm biomass was not burnt but windrowed and this caused very high propagation of rhinoceros beetles, the most severe pest in immature and young mature palms, and severe crop loss in the first year of harvest due to beetle damage incidence. Nutrients in windrowed oil palm fronds are not readily accessible to replanted palms until the palm roots reached the windrows. The zero burning technique requires specialized machines. Heavy machinery caused damage to plantation roads and compaction of the soil which reduces its fertility to newly planted seedlings. A tractor mounted mulcher was designed and produced by Howard Company which is cheaper and more convenient than the heavy mulchers but farmers were complaining on the mulcher performance despite its evaluation. This thesis focusses on the development and field performance of mulcher blades by cutting and incorporating the oil palm fronds/trunks into the soil during replanting period. Three different blades were developed with different geometries and lifting angles, both the modified and the original blade were tested and compared the performance. The effects of different blades with respect to noise, actual tractor PTO speed, vibration, degree of mulching, mulching depth, actual tractor forward speed, torque, power, and fuel consumption in mulching oil palm fronds were analyzed statistically. Mathematical equations were also developed to predict mulching power of the blades. The blades were drawn and developed using Solid Works software.Tests were done at the Universiti Putra Malaysia oil palm plantation, under the same operating conditions using four blades with 0o, 60o, 120o, and 150o lifting angles, two tractor PTO speeds (540 and 1000 rpm) and three tractor forward speeds (1, 3, and 5 km/h). Bulk density and moisture content of the experimental plots were also measured at 20 cm from the surface level of the experimental plot before the experiment. Similarly, oil palm frond moisture contents prior to mulching were also determined. Tractor torque meter Kistler model was used to collect data on torque, power, and actual tractor PTO speed. The experimental plots were designed in a randomized complete block design (RCBD) at three factors. ANOVA was used to analyze significant and non-significant treatment effects and Tukey's Studentized Range (HSD) test was used to determine significance between the means (P<0.05) using statistical analysis systems (SAS 9.2) 2010 software. The statistical analysis results also indicated that minimum noise effect on operator with level of 70.10 dB(A) was obtained at tractor forward speed of 5 km/h and tractor PTO speed of 1000 rpm using blade with 60o lifting angle. The minimum vibration was given by blade with 0o lifting angle at tractor forward speeds of 1 and 3 km/h and tractor PTO speeds of 540 and 1000 rpm with mean values of 0.47 and 0.50 Hz respectively. Degree of Mulching was best obtained by the blade with 120o lifting angle at tractor forward speeds of 1 and 5 km/h and tractor PTO speeds of 1000 and 540 rpm, with mean values of 63.15 and 89.67 % accordingly. The mean value for mulching depth was best recorded by the blade with 120o lifting angle at 14.20 cm with tractor forward speed of 3 km/h and at tractor PTO speed of 1000 rpm. Minimum torque requirement of 10.00 Nm was obtained for mulching oil palm fronds by blade with 0o lifting angle at tractor forward speed of 3 km/h and at tractor PTO speed of 1000 rpm. Power consumption of mulching blade with 0ᵒ lifting angle increased from 0.98 to 1.07 kW at tractor forward speed of 5 km/h when the PTO speed increased from 540 to 1000 rpm. Similarly, the power consumption of the mulching blade with 60ᵒ lifting angle increased from 2.04 to 2.47 kW at tractor forward speed of 3 km/h when the tractor PTO speed was increased from 540 to 1000 rpm. Optimum fuel consumption for mulching oil palm fronds was 1.52 l/ha best obtained at tractor PTO speed of 1000 rpm and tractor forward speed of 1 km/h. using blade with 0o lifting angle. Model development for mulching power prediction revealed that quadratic regression analysis indicates a highly significant and the intercept, was also highly significant. The quadratic effect of power on mulching oil palm fronds indicates that approximately 97.4 % of the variance in power is obtainable by blade lifting angles.